Sex Differences in Cardiovascular Outcomes of Older Adults After Myocardial Infarction - Kerola Anne M; Palomäki Antti; Rautava Päivi; Nuotio Maria; Kytö Ville (United States, 2022)
Background Evidence on the impact of sex on prognoses after myocardial infarction (MI) among older adults is limited. We evaluated sex differences in long-term cardiovascular outcomes after MI in older adults. Methods and Results All patients with MI ≥70 years admitted to 20 Finnish hospitals during a 10-year period and discharged alive were studied retrospectively using a combination of national registries (n=31 578, 51% men, mean age 79). The primary outcome was combined major adverse cardiovascular event within 10-year follow-up. Sex differences in baseline features were equalized using inverse probability weighting adjustment. Women were older, with different comorbidity profiles and rarer ST-segment-elevation MI and revascularization, compared with men. Adenosine diphosphate inhibitors, anticoagulation, statins, and high-dose statins were more frequently used by men, and renin-angiotensin-aldosterone inhibitors and beta blockers by women. After balancing these differences by inverse probability weighting, the cumulative 10-year incidence of major adverse cardiovascular events was 67.7% in men, 62.0% in women (hazard ratio [HR], 1.17; CI, 1.13-1.21; P<0.0001). New MI (37.0% in men, 33.1% in women; HR, 1.16; P<0.0001), ischemic stroke (21.1% versus 19.5%; HR, 1.10; P=0.004), and cardiovascular death (56.0% versus 51.1%; HR, 1.18; P<0.0001) were more frequent in men during long-term follow-up after MI. Sex differences in major adverse cardiovascular events were similar in subgroups of revascularized and non-revascularized patients, and in patients 70 to 79 and ≥80 years. Conclusions Older men had higher long-term risk of major adverse cardiovascular events after MI, compared with older women with similar baseline features and evidence-based medications. Our results highlight the importance of accounting for confounding factors when studying sex differences in cardiovascular outcomes.